BITI NA VULKANU CIVILIZACIJE / BEAING ON THE VOLCANO OF THE CIVILIZATION: ULRICH BECK, ANTHONY GIDDNES I ZYGMUNT BAUMAN O ONTOLOŠKOJ (NE)SIGURNOSTI / ULRICH BECK, ANTHONY GIDDENS AND ZYGMUNT BAUMAN ON THE ONTOLOGICAL (IN)SECURITY - Tadić, Tomislav (SOPHOS: A Young Researchers’ Journal, 2021)
In this paper I emphasise the problem of ontological (in)security in the context of contemporary world events related to the sudden expansion of COVID-19 virus. The emphasis is on the tradition of the reflexive sociology and the concept of methodological pluralism. The question of ontological (in)security is analysed form three sociological optics: 1) Ulrich Bech’s thesis on “risk society”; 2. Anthony Giddinese's thesis on “radicalised consequences of modernity”; 3. Zygmunt Bauman’s theory of the “liquid modernity”. Paper indicates that all three sociological theories are treating ontological (in)security as central concept, and implies that there is necessary correlation between ontological insecurity and the question of the modernity and its character.